Peningkatan Produksi Pangan pada Lahan Sawah dengan Penerapan Pemupukan Hara Spesifik Lokasi (PHSL) Melalui Evaluasi Status Unsur Hara Tanah - I NYOMAN SUNARTA; I NYOMAN MERIT; NI MADE TRIGUNASIH; TATIEK KUSMAWATI (Fakultas Pertanian Universitas Udayana, 2015)
An Increase of The Yield of Paddy Rice with Application of The Site-Specific NutrientFertilization (SSNF) through Evaluation of The Nutrient Soil Status. Agricultural landincluding paddy fields decreases every year due to land conversion and decreasing of waterresources for irrigation. However, the need for food (rice) increases simultaneously with theincreasing of population growth. Although inorganic fertilizer and improved varieties of ricehave been intensively used, however, expected rice production has not been achieved.Fertilization based on site-specific nutrient might require for solving the problems. Researchconcerning of the site-specific nutrient fertilization (SSNF) have been carried out at Megati,District of Selemadeg Timur Tabanan Regency from April to October 2015. The objective ofthe research was to find out the effects of several types of fertilization with differentcomposition on the growth and yield of rice. The treatments were Kd0P0 (without fertilizer),Kd0P1 ( without organic fertilizer ; 100 kg urea, 25 kg SP36,and 25 kg KCl ha-1), Kd0P2(without organic fertilizer ; 150 kg urea, 50 kg SP36 and 50 kg KCl ha-1), Kd0P3 (withoutorganic fertilizer; 200 kg urea, 75 kg SP36 dan 75 kg KCl ha-1), Kd1P1 ( 5 tons of organicfertilizer ha-1; 100 kg urea, 25 kg SP36,and 25 kg KCl ha-1 ), Kd1P2 ( 5 tons of organicfertilizer ha-1; 150 kg urea, 50 kg SP36 and 50 kg KCl ha-1 ), Kd1P3 (5 tons of organicfertilizer ha-1; 200 kg urea, 75 kg SP36 and 75 kg KCl ha-1 ), and SSNF (5 tons of organicfertilizer ha-1; Rainbow NPK 200 kg ha-1 and 75 kg urea ha-1). The results showed that theplant height and the highest number of productive tillers was obtained from Kd1P3 treatment.The highest yield was obtained from the SSNF treatment. The SSNF treatment produced 9.12ton dried grain ha-1.